Tanggung Jawab Direksi Pada Perseroan Terbatas Milik Badan Usaha Milik Negara - Tasya Nailul Fikriya (Universitas Islam Indonesia, 2020)
This study focuses on the responsibilities of the Board of Directors in the event of a financial loss to a limited liability company in the form of State-Owned Enterprises (BUMN). The purpose of this research is to identify two issues, first, the legal responsibility of the company directors in a Limited Liability Company (PT), and second, whether the loss of the management of a Limited Liability Company can be seen as a loss to the State. The method used is normative juridical. The results of the study concluded that the legal responsibility of the company directors in a Limited Liability Company (PT), is based on the principle that each member of the Board of Directors is fully responsible personally for the loss of the Company if the person concerned is guilty or negligent in carrying out his duties. Separation of state assets from the State Revenue and Expenditure Budget (APBN) to be subsequently used as capital in BUMN (company), does not cause a break in the legal relationship between the state and the BUMN, given the state's position as a legal subject that owns shares (majority) in BUMN in the form of a company.